2017
DOI: 10.1097/coc.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Patterns of Local, Regional, and Distant Failure in Squamous Cell Carcinoma of the Vulva

Abstract: Stromal invasion >2 mm and lymph node extracapsular spread are the most important factors predicting for local and regional failure, respectively. Studies evaluating the effectiveness of adjuvant treatment in high-risk patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…4 In addition, a large study suggested that tumor diameter is an important predictor for recurrence. 1 A relationship between deep stromal invasion and recurrence was shown in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 In addition, a large study suggested that tumor diameter is an important predictor for recurrence. 1 A relationship between deep stromal invasion and recurrence was shown in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 A relationship between deep stromal invasion and recurrence was shown in some studies. 4,13,16 Although Bogani et al found the difference using the cutoff value of 2 mm for stromal invasion, Iacopani et al 13 used the cutoff value of 4 mm to show the significant correlation between stromal invasion and recurrence. In our study, stromal invasion greater than 9 mm was associated with local and inguinal recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 30-40% of vulvar cancer patients are in stage III-IV at presentation (7)(8)(9). The rate of urethral involvement is not defined in literature, but it is underestimated.…”
Section: Introductionmentioning
confidence: 99%